2019
DOI: 10.1109/access.2019.2907815
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured Text Resource Access Control Attribute Mining Technology Based on Convolutional Neural Network

Abstract: In the attribute-based access control (ABAC) model, attributes are the basis for controlling access to data resources. The existing attribute extraction methods that are based on manual management are time consuming and have a high cost, variable accuracy, and poor scalability when dealing with massive unstructured text from big data resources. This paper proposes a multidimensional hybrid feature generation method for text resource attributes. The method comprehensively calculates the characteristics of attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In order to process an image for recognition, several parameters are collected from that image's features and compared with the existing library. A similarity value is obtained based on the proposed model, which is then used to identify the identity based on the calculated value for the face [35]. Fig.…”
Section: System Designmentioning
confidence: 99%
“…In order to process an image for recognition, several parameters are collected from that image's features and compared with the existing library. A similarity value is obtained based on the proposed model, which is then used to identify the identity based on the calculated value for the face [35]. Fig.…”
Section: System Designmentioning
confidence: 99%
“…Used in # of studies Percentage ABAC [23], [24], [25], [26], [12], [27], [28], [29], [10], [30], [31], [32], [33], [34], [13], [35], [36] and MLBAC were each used in one study (2%). Some studies may have employed multiple access control models, such as [25], which utilized both ABAC and ReBAC.…”
Section: Ac Modelmentioning
confidence: 99%
“…Metrics like AUC, ROC, and FNR were employed in two studies each, and the remaining metrics were reported only once. It is important to note that multiple [23], [41], [44], [53], [45], [24], [42], [70], [39], [56], [46], [26], [71], [64], [40], [28], [43], [66], [10], [30], [31], [47], [62], [33], [76], [13], [37], [67] 28 45 % Accuracy [52], [53], [70], [39], [65], [12], [71], [72], [64], [40], [57], [28], [43], [66], [59], [10], [61], [38], [48], [8], [62],…”
Section: H Performance Metrics (Rq8)mentioning
confidence: 99%
“…In this paper [1] author proposed a multidimensional hybrid feature strategy for text resource properties. This technique completely figures the qualities of characteristics themselves, the connections among attributes, and the connection between…”
Section: Literature Reviewmentioning
confidence: 99%